Spontaneous Rupture of Unscarred Uterus in Second Trimester Pregnancy Presented as Acute Appendicitis; An Unusual Obstetric Emergency and the Importance of Imaging in Suspected Acute Appendicitis in Pregnancy - A.S Ahmad Shariffuddin, Fadya Nabiha; Bahari, Nur Bazlaah; Abu Bakar, Hirdayu; Salekan, Khairuzi; Mohd Isam, Fazlin Farhana; Sulaiman, Syariz Ezuan; Dzulkifli , Muhammad Amer Dad (IIUM Medical Journal Malaysia, 2022)
Spontaneous uterine rupture in an unscarred uterus in early trimester is very rare and difficult to diagnose. We reported a case of 28 years old lady at 15th week of gestation with three previous uneventful obstetrical history presented with one-day history of acute right iliac fossa pain and vomiting. She was subjected for an open appendectomy after an assessment by obstetric and surgical team which revealed ruptured of uterine fundal. She recovered well but she lost her pregnancy. Traditional management of acute appendicitis in pregnant patients is an early exploration. However recent studies showed that it was unpractical as the rate of pregnancies loss was two times with negative appendectomy compared to simple appendicitis; and almost as high as complicated appendicitis. All suspected appendicitis cases required ultrasound studies, and when the diagnosis is uncertain, further imaging such as computed tomography (CT) scan or magnetic resonance imaging is needed prior to surgery.